The Clinical Efficacy of Infrared Photocoagulation Versus Closed Hemorrhoidectomy in Treatment of Hemorrhoid - Nikshoar, Mohammad Reza; Maleki, Zahra; Nemati Honar, Behzad (Journal of Lasers in Medical Sciences, 2017)
Introduction: Infrared photocoagulation (IRC) was introduced as a mainstay procedure for treatment of hemorrhoids. The present study aimed to compare the clinical efficacy of IRC compared to closed hemorrhoidectomy. Methods: Forty patients suffering grade-3 hemorrhoid that referred to the surgery clinic at Imam Hossein hospital in Tehran in 2013 were randomly assigned to groups treated with the IRC modality or Ferguson’s closed hemorrhoidectomy method. The patients in the 2 groups were followed-up for the first 24 hours after surgery and 8 weeks later. Postoperative pain was assessed using visual analogue scale (VAS) at three time points of 24 hours, 2 weeks and 8 weeks after operation. Results: Regarding bleeding, its overall prevalence was 5.0% in the IRC group and 30.0% in the hemorrhoidectomy group, which was significantly less prevalent in the IRC group. Notably, the IRC group had a lower mean postoperative pain score compared to the hemorrhoidectomy group. Time of return to work was significantly shorter in the IRC group; no difference was found in the mean duration of hospital stay, and recurrence rate across 2 groups. Conclusion: IRC procedure is safer than closed hemorrhoidectomy with lower postoperative pain severity, less secondary bleeding, and leads to earlier return to work in patients with hemorrhoid.